Fabrication and performances of microencapsulated palmitic acid with enhanced thermal properties - Latibari S.T.; Mehrali M.; Mehrali M.; Mahlia T.M.I.; Metselaar H.S.C. (American Chemical Society, 2023)
Alumina; Aluminum hydroxide; Aluminum oxide; Fabrication; Microencapsulation; Microstructure; Palmitic acid; Phase change materials; Saturated fatty acids; Sol-gel process; Sol-gels; Specific heat; Thermodynamic stability; Aluminum isopropoxides; Encapsulation efficiency; Enhanced thermal conductivity; High thermal conductivity; Microencapsulated phase change material; Stability enhancement; Storage potential; Thermal effusivity; Thermal conductivity